Social Embeddedness of Pro-Environment Fisherman Community in The Use of Eco-Friendly Fishing Gear Technology at Drini Beach Gunung Kidul Yogyakarta - Kristina Situmeang, Marini; Slamet, Yulius; Tri Kartono, Drajat (Udayana Journal of Social Sciences and Humanities; Vol 1 No 2 (2017): UJoSSH, September 2017, 2017)
This study aims to determine to what extent the knowledge of the fishing communities of Gunung Kidul Yogyakarta in interpreting the use of environmentally friendly fishing technology. Also, to analyze how the form of social embeddedness related to the conservation of environmentally friendly fishing gear is seen from the dimensions of relational relationships and structural relationships in the context of social networks Coastal fishermen community Drini Gunung Kidul Yogyakarta. This study uses the sociology theory of economics from Granovetter on Social Embeddedness in "The New Economic Sociology". The research method was conducted qualitatively with phenomenology approach. The data collection was done by observation and in-depth interview. The results show that the understanding of fishing communities related to the use of environmentally friendly fishing gear technology cannot be separated from the existing social network of fishers. In the relational dimension of conservation form among fishers skipper, fisherman and fisherman who form a cooperative relationship in the fulfillment of daily necessities, including in the face of famine season, so that no fisher is desperate to use environmentally friendly fishing gear to get personal benefit Only. Meanwhile, in the structural dimension or fisherman institution, the rules on marine environment management including conservation of environmentally friendly fishing gear are among the cooperative units, and fishermen organizations under the supervision of the Office of Marine and Fishery of Yogyakarta by holding socialization and fish catching operation every three times in a year.